Immunoglobulin G-dependent inhibition of inflammatory bone remodeling requires pattern recognition receptor Dectin-1 - Seeling, Michaela; Pöhnl, Matthias; Kara, Sibel; Horstmann, Nathalie; Riemer, Carolina; Wöhner, Miriam; Liang, Chunguang; Brückner, Christin; Eiring, Patrick; Werner, Anja; Biburger, Markus; Altmann, Leon; et al. (Immunity, 2023)
Immunoglobulin G (IgG) antibodies are major drivers of inflammation during infectious and autoimmune diseases. In pooled serum IgG (IVIg), however, antibodies have a potent immunomodulatory and anti-inflammatory activity, but how this is mediated is unclear. We studied IgG-dependent initiation of resolution of inflammation in cytokine- and autoantibody-driven models of rheumatoid arthritis and found IVIg sialylation inhibited joint inflammation, whereas inhibition of osteoclastogenesis was sialic acid independent. Instead, IVIg-dependent inhibition of osteoclastogenesis was abrogated in mice lacking receptors Dectin-1 or FcγRIIb. Atomistic molecular dynamics simulations and super-resolution microscopy revealed that Dectin-1 promoted FcγRIIb membrane conformations that allowed productive IgG binding and enhanced interactions with mouse and human IgG subclasses. IVIg reprogrammed monocytes via FcγRIIb-dependent signaling that required Dectin-1. Our data identify a pathogen-independent function of Dectin-1 as a co-inhibitory checkpoint for IgG-dependent inhibition of mouse and human osteoclastogenesis. These findings may have implications for therapeutic targeting of autoantibody and cytokine-driven inflammation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: bone; Dectin-1; Fc-receptor; glycosylation; IgG; inflammation; osteoclast; rheumatoid arthritis

Lipid Bicelles in the Study of Biomembrane Characteristics - Pöhnl, Matthias; Kluge, Christoph; Böckmann, Rainer (Journal of Chemical Theory and Computation, 2023)
Simulations of lipid membranes typically make use of periodic boundary conditions to mimic macroscopically sized membranes and allow for comparison to experiments performed e.g. on planar lipid membranes or on unilamellar lipid vesicles. However, the lateral periodicity partly suppresses membrane fluctuations or membrane remodeling, processes that are of particular importance in the study of asymmetric membranes-i.e. membranes with integral or associated proteins and/or asymmetric lipid compositions. Here, we devised a simple albeit powerful lipid bicelle model system that (i) displays similar structural, dynamical, and mechanical properties compared to infinite periodic lipid membrane systems and allows (ii) for the study of asymmetric lipid bilayer systems and (iii) the unperturbed formation of local spontaneous curvature induced by lipids or proteins in molecular dynamics simulations. In addition, the system is characterized by largely unbiased thermal fluctuations as opposed to standard bilayer systems. Application of the bicelle system for an asymmetric lipid composition resembling the plasma membrane reveals that the cholesterol density for a tension-free plasma membrane with a vanishing spontaneous curvature is larger by 28% within the extracellular leaflet compared to the cytosolic leaflet.
CRIS-Team Scopus Importer:2023-03-24

Lipid nanodiscs as a tool to unlock membrane dynamics - Pöhnl, Matthias; Böckmann, Rainer (EUROPEAN BIOPHYSICS JOURNAL WITH BIOPHYSICS LETTERS, 2021)
CRIS-Team WoS Importer:2021-08-13

Nanoscale structure of biomembranes - Bochicchio, Anna; Gahbauer, Stefan; Pöhnl, Matthias; Böckmann, Rainer (EUROPEAN BIOPHYSICS JOURNAL WITH BIOPHYSICS LETTERS, 2019)
CRIS-Team WoS Importer:2019-07-19

Nonuniversal impact of cholesterol on membranes mobility, curvature sensing and elasticity - Pöhnl, Matthias; Trollmann, Marius; Böckmann, Rainer (Nature Communications, 2023)
Biological membranes, composed mainly of phospholipids and cholesterol, play a vital role as cellular barriers. They undergo localized reshaping in response to environmental cues and protein interactions, with the energetics of deformations crucial for exerting biological functions. This study investigates the non-universal role of cholesterol on the structure and elasticity of saturated and unsaturated lipid membranes. Our study uncovers a highly cooperative relationship between thermal membrane bending and local cholesterol redistribution, with cholesterol showing a strong preference for the compressed membrane leaflet. Remarkably, in unsaturated membranes, increased cholesterol mobility enhances cooperativity, resulting in membrane softening despite membrane thickening and lipid compression caused by cholesterol. These findings elucidate the intricate interplay between thermodynamic forces and local molecular interactions that govern collective properties of membranes.
CRIS-Team Scopus Importer:2023-12-22

On the loss of inhibitory function due to FcgRIIB-I232T transmembrane polymorphism - Pöhnl, Matthias; Nimmerjahn, Falk; Böckmann, Rainer (EUROPEAN BIOPHYSICS JOURNAL WITH BIOPHYSICS LETTERS, 2021)
CRIS-Team WoS Importer:2021-08-13

Spontaneous local membrane curvature induced by transmembrane proteins - Kluge, Christoph; Pöhnl, Matthias; Böckmann, Rainer (Biophysical Journal, 2022)
The (local) curvature of cellular membranes acts as a driving force for the targeting of membrane-associated proteins to specific membrane domains, as well as a sorting mechanism for transmembrane proteins, e.g., by accumulation in regions of matching spontaneous curvature. The latter measure was previously experimentally employed to study the curvature induced by the potassium channel KvAP and by aquaporin AQP0. However, the direction of the reported spontaneous curvature levels as well as the molecular driving forces governing the membrane curvature induced by these integral transmembrane proteins could not be addressed experimentally. Here, using both coarse-grained and atomistic molecular dynamics (MD) simulations, we report induced spontaneous curvature values for the homologous potassium channel Kv 1.2/2.1 Chimera (KvChim) and AQP0 embedded in unrestrained lipid bicelles that are in very good agreement with experiment. Importantly, the direction of curvature could be directly assessed from our simulations: KvChim induces a strong positive membrane curvature (≈0.036 nm−1) whereas AQP0 causes a comparably small negative curvature (≈−0.019 nm−1). Analyses of protein-lipid interactions within the bicelle revealed that the potassium channel shapes the surrounding membrane via structural determinants. Differences in shape of the protein-lipid interface of the voltage-gating domains between the extracellular and cytosolic membrane leaflets induce membrane stress and thereby promote a protein-proximal membrane curvature. In contrast, the water pore AQP0 displayed a high structural stability and an only faint effect on the surrounding membrane environment that is connected to its wedge-like shape.
CRIS-Team Scopus Importer:2022-03-11